Understanding older adults’ attitudes toward mobile and wearable technologies to support health and cognition - Fowe, Ibukun E.; Boot, Walter R. (Frontiers in Psychology, 2022)
The use of technology to facilitate remote patient monitoring and virtual care is desirable due to the challenges of providing healthcare during the COVID-19 pandemic and the need for more efficient and effective methods to care for the expanding older adult population. Further, the collection and sharing of patient generated health data (PGHD) through these technologies holds promise with respect to improving outcomes and reducing the cost of care by facilitating the early detection and treatment of cognitive and health problems. Despite the potential benefits of these technologies, their promise might be hampered by low rates of acceptance and adoption among older adults. In an online survey, we assessed community-dwelling older adults’ (N = 92) attitudes towards the use of wearable and mobile technologies for 1) predicting cognitive decline, 2) assisting with adherence to healthy activities, and 3) collecting self-report data to understand current and predict future health states. Participants generally agreed hypothetical technology solutions would be useful (M = 4.20, SD = .70 on a 1-5 agreement scale; 5 = “strongly agree”), that they were interested in learning more about these technologies (M = 4.04, SD = .74), and that they would be willing to adopt these technologies (M = 3.83, SD = .93), though attitudes varied. Although participants were generally positive toward these technologies, they were relatively neutral in terms of their agreement that privacy of generated data was a concern (M = 2.92, SD = 1.02). Privacy concerns were associated with lower interest and willingness to adopt. More positive general technology attitudes and higher mobile device proficiency were associated with greater acceptance and willingness to adopt these technologies. Finally, poorer self-rated health was related to negative attitudes toward these technologies. These findings highlight barriers and potential targets for intervention to increase uptake of these and similar technologies among older adults who may be reluctant to adopt remote monitoring technologies.